HEALTH IMPACT OF TOBACCO SMOKING: CARDIOVASCULAR, RESPIRATORY AND NEOPLASTIC DISEASES - Paweł Liszka; Michał Ziemba; Klaudia Zackiewicz; Agata Wińska; Oliwia Sędziak; Hanna Pietruszewska; Agata Ogórek; Julianna Zielska; Katarzyna Kleszczewska; Izabela Majchrzak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Smoking remains one of the leading preventable causes of premature mortality worldwide. A structured search of PubMed and Google Scholar databases was performed to identify clinical, epidemiological and experimental evidence, including original studies, systematic reviews and meta-analyses, on the impact of active and passive smoking. This narrative review summarises current evidence on the health effects of tobacco smoking and secondhand smoke exposure, with a particular focus on cardiovascular, respiratory and neoplastic diseases. Description of the state of knowledge: Tobacco smoke contains numerous toxic and carcinogenic compounds that promote endothelial dysfunction, oxidative stress and chronic inflammation, thereby accelerating atherosclerosis and increasing the risk of myocardial infarction, stroke and other vascular events. Long-term exposure damages the airways and lung parenchyma, leading to chronic obstructive pulmonary disease (COPD), worse asthma control and increased susceptibility to respiratory infections. Smoking is also a major driver of cancer, accounting for most lung cancer cases and contributing substantially to malignancies of the upper aerodigestive tract, pancreas and bladder. Secondhand smoke, although involving lower levels of exposure, is associated with higher risks of cardiovascular disease, respiratory illness, type 2 diabetes and adverse outcomes in children and older adults. Conclusion: The available evidence clearly shows that there is no safe level of exposure to tobacco smoke. Smoking cessation and effective protection from secondhand smoke are essential components of strategies to prevent cardiovascular, respiratory and neoplastic diseases and should remain central priorities in public health policy and clinical practice.